Effect of putrescine and benzyl adenine on growth, flowering and post-harvest keeping quality parameters in chrysanthemum (Chrysanthemum morifolium Ramat.) - Singh, Taranjit; Bala, Madhu (Journal of Horticultural Sciences, 2020)
The experiment was conducted with the objective to study the effect of different anti-senescence compounds like putrescine and benzyl adenine (BA) on vegetative, floral, and post-harvest keeping quality of chrysanthemum cv. Punjab Shyamli. The experiment was conducted in a randomized block design (RBD) and replicated thrice. Putrescine (@ 50, 100, and 150 ppm) and benzyl-adenine (@ 100, 150, and 200 ppm) were sprayed twice on cv. Punjab Shyamli (spray type and pompon) at bud initiation stage and at fully developed flower buds. Control plants were sprayed with normal water. Floral parameters were delayed and the vase life of cut stems was enhanced by benzyl adenine @ 200 ppm. The maximum delay of flower opening stage (116.33 days), number of sprays (5.00), and vase life (27.22 days) were obtained with benzyl-adenine @ 200 ppm treatment. The flower diameter was 4.53 cm with benzyl-adenine @ 200 ppm compared to 2.87 cm in control.